Natural compound Alternol exerts a broad anti-cancer spectrum and a superior therapeutic safety index in vivo - He, Chenchen; Ma, Linlin; Hirst, Jeff; Li, Fei; Wu, Hao; Liu, Wang; Zhao, Jiang; Xu, Feng; Godwin, Andrew K.; Wang, Xiangwei; Li, Benyi (Frontiers in Pharmacology, 2024)
Alternol is a natural compound isolated from the fermentation of a mutated fungus. We have demonstrated its potent anti-cancer effect via the accumulation of radical oxygen species (ROS) in prostate cancer cells in vitro and in vivo. In this study, we tested its anti-cancer spectrum using the National Cancer Institute-60 (NCI-60) screening, a protein quantitation-based assay. Our results showed that Alternol exerted a potent anti-cancer effect on 50 (83%) cancer cell lines with a GI50 less than 5 M and induced a lethal response in 12 (24%) of those 50 responding cell lines at 10 M concentration. Consistently, Alternol displayed a similar anti-cancer effect on 14 ovarian cancer cell lines in an ATP quantitation-based assay. Most interestingly, Alternol showed an excellent safety profile with a maximum tolerance dose (MTD) at 665 mg/kg bodyweight in mice. Its therapeutic index was calculated as 13.3 based on the effective tumorsuppressing doses from HeLa and PC-3 cell-derived xenograft models. Taken together, Alternol has a broad anti-cancer spectrum with a safe therapeutic index in vivo.